Implementing six sigma : smarter solutions using statistical methods - Breyfogle, Forrest W., 1946- (Wiley, 2003)
* Includes new and expanded coverage of Six Sigma infrastructure building and benchmarking. * Provides plans, checklists, metrics, and pitfalls.